Enantioselective copper-catalysed defluorosilylation of trifluoro-methylated alkenes with silylboronates. Issue 18 (12th August 2020) - Gao, Pan; Gao, Liuzhou; Xi, Longlong; Zhang, Zedong; Li, Shuhua; Shi, Zhuangzhi
Abstract : An efficient method for the construction of gem -difluoroallylsilanes with high enantiomeric excess via a copper-catalysed defluorosilylation of trifluoromethylated alkenes with silylboronates is described. Abstract : An efficient method for the construction of gem -difluoroallylsilanes with high enantiomeric excess via a copper-catalysed defluorosilylation of trifluoromethylated alkenes with silylboronates is described. The key to this high enantioselectivity is the careful selection of NaOH as the base and using a triazolium-based chiral N-heterocyclic carbene (NHC) as a ligand in the presence of a copper catalyst. The reaction conditions are mild, and excellent functional group compatibility is observed. This strategy addresses the limitations of the previously described base-mediated defluorosilylation under transition metal-free conditions, which can lead to erosion of the enantioselectivity. The synthetic utilities of the obtained gem -difluoroallylsilanes are also presented. Computational and experimental data suggest that the reaction proceeds through the enantioselective insertion of silyl-Cu/NHC species into the double bond of trifluormethyl alkenes and the Cu-mediated β-F elimination steps.